Camacho Zegarra, María, Fiedler, Denise y González-Palacios, Carlos (coords.). Seguridad y libertad - González -Palacios, Carlos Alberto (2020)
Published in Lima, but with contributions from authors from different countries from Latin America and Europe, this book presents a large part of the works exposed during the IV Peruvian-Franco-German Academic Meeting that in August 2017 brought together the Faculties of Law of the Technische Universität Dresden (Germany), from the Université Paris-Nanterre (France) and the ESAN University around the topic «Security and freedom ». This book consists of thirteen articles in various languages, spread over five chapters representing the current challenges of our democracies contemporary: I. The legal implications of the state of emergency. II. Security and migration borders. III. Terrorism, a changing threat. IV. Security issues in international law. V. Fight against corruption.